2013
DOI: 10.4103/0019-509x.112270
|View full text |Cite
|
Sign up to set email alerts
|

Socio demographic profile of oral cancer patients residing in Tamil Nadu - A hospital based study

Abstract: Identifying occupation, income and education specific disparities in tobacco use can provide a useful "signspot" indicating inequalities that need to be addressed by policy makers and broader community through allocation of resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
2
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 11 publications
5
23
2
6
Order By: Relevance
“…The youngest being 28 years and the eldest is 76 years. This is in accordance with Ganesh et al, 20 Bhardwaj et al 21 In the present study, 20 patients were in the age group of 31 to 40 years followed by 15 in the group of 51-60 years. The incidence of oral cancer in younger age group is increasing due to the habit of gutkha and pan masala chewing.…”
Section: Discussionsupporting
confidence: 93%
“…The youngest being 28 years and the eldest is 76 years. This is in accordance with Ganesh et al, 20 Bhardwaj et al 21 In the present study, 20 patients were in the age group of 31 to 40 years followed by 15 in the group of 51-60 years. The incidence of oral cancer in younger age group is increasing due to the habit of gutkha and pan masala chewing.…”
Section: Discussionsupporting
confidence: 93%
“…The is compared with other similar studies. [17,18] The results of the study for the presenting symptoms of SCC of the gingivobuccal complex can be compared with those of the study conducted by Sharma et al [19] This study found that the most common clinical symptom at presentation was oral ulcer (76%), pain at local site (43%) and swelling/ growth (33%). [19] In the present study, the most common substance abuse was tobacco use (in any form other than smoking; 70%) followed by alcohol abuse (63.33%) and smoking (33.33%).…”
Section: Discussionmentioning
confidence: 84%
“…It was found that, in developing countries, there is a high percentage of patients with oral cancer belonging to less favored socioeconomic classes [25]. According to the authors, this finding is clearly associated with the difficulties in accessing health systems, possibly incurring advanced clinical stages.…”
Section: Discussionmentioning
confidence: 99%